Luteolin Reduces Alzheimer’s Disease Pathologies Induced by Traumatic Brain Injury - Sawmiller, Darrell (Molecular Diversity Preservation International (MDPI), 2014)
Traumatic brain injury (TBI) occurs in response to an acute insult to the head and is recognized as a major risk factor for Alzheimer’s disease (AD). Indeed, recent studies have suggested a pathological overlap between TBI and AD, with both conditions exhibiting amyloid-beta (Aβ) deposits, tauopathy, and neuroinflammation. Additional studies involving animal models of AD indicate that some AD-related genotypic determinants may be critical factors enhancing temporal and phenotypic symptoms of TBI. Thus in the present study, we examined sub-acute effects of moderate TBI delivered by a gas-driven shock tube device in Aβ depositing Tg2576 mice. Three days later, significant increases in b-amyloid deposition, glycogen synthase-3 (GSK-3) activation, phospho-tau, and pro-inflammatory cytokines were observed. Importantly, peripheral treatment with the naturally occurring flavonoid, luteolin, significantly abolished these accelerated pathologies. This study lays the groundwork for a safe and natural compound that could prevent or treat TBI with minimal or no deleterious side effects in combat personnel and others at risk or who have experienced TBI.